Promoting meaningful learning via an online project-based module / Ashfahani Zakaria, Amla Mohd. Salleh, Mohd. Arif Ismail, Simin Ghavifekr - Zakaria, Ashfahani; Mohd. Salleh, Amla; Ismail, Mohd. Arif; Ghavifekr, Simin (UiTM Press, 2017)
This paper will discuss the use of an Online Project-based Module (m-PAT) to promote meaningful learning among students using the project-based learning approach. m-PAT was applied in a project-based learning for a topic in Physics. A mixed method case study design was employed, where the findings of quantitative data were confirmed using the findings of qualitative data. A total of 42 form four students from a secondary school in Klang Valley, Malaysia were chosen based on purposive sampling. The data were collected through questionnaire, student reflection, online discussion, and open-ended questions after each participant generated a physics-learning blog by using the m-PAT as a platform. Quantitative data were analyzed descriptively in form of mean scores and standard deviations to observe the distribution of students’ feedback towards the attributes for meaningful learning during the m-PAT implementation. Thematic analysis was used for the qualitative data to produce a tabulated matrix related to the attributes of meaningful learning. The findings prove that m-PAT has a high potential as an online platform to promote a meaningful learning for students. Further research with a larger number of participants is needed to support the present findings.